Effect of Dissolution and Dispersion Conditions of VC-713 on the Hydrate Inhibition. (27th March 2019) - Wang, Ren; Sun, Huicui; Sun, Jinsheng; Qu, Yuanzhi; Zhang, Jie; Shi, Xiaomei; Zhang, Ling; Guo, Dongdong
Abstract : VC-713 is a kind of hydrate kinetics inhibitor, which is widely used because of its strong hydrate inhibition. In this paper, VC-713 was dissolved and dispersed into its solution to various degrees by stirring the solution at the speeds of 600 r·min −1 and 12000 r·min −1 . Then, under the condition of normal pressure and temperature change (gradually decreasing from 278.15 K to 273.65 K), the hydrate inhibitory effect of dissolution and dispersion of VC-713 on THF hydrate formation was studied. The variation in the concentration of VC-713 was monitored during the experiments. In addition, the mesoscopic structure characteristics of aqueous solutions were observed, and experimental phenomena in the reactor were recorded along with real time. Then, the experimental data were comprehensively analyzed, and the underlying mechanism of inhibition was revealed. Results showed that VC-713 inhibits hydrate nucleation and growth by adsorbing and binding. When the addition amounts are the same, better dissolution and dispersion of VC-713 can inhibit the hydrate formation more effectively. This is due to more complex skeleton structures formed by the hydrated VC-713 molecule. When the amount of VC-713 is 0.5 wt.%, the induction time, the formation rate, and the degree of supercooling of hydrate formation were extended, mitigated, and increased by 10.30%, 21.43%, and 17.80%, respectively, and changed to values of 8.75%, 14.29%, and 22.50%, respectively, for 1.0 wt.% VC-713.